Explore and measure brand love, and its antecedents and consequences, among portuguese consumers - Rodrigues, Maria João Lima (2020)
Relationship marketing is crucial in 21th Century. Thus, companies start to focus their attention on the relationships with their consumers, rather than expose the consumer to a product/service. This, led to the increase of relevance of some concepts beyond the literature, being Brand Love, one of them. Therefore, the present dissertation aims to explore the antecedents and consequences of Brand Love in Portugal, with the purpose of understand how brands can establish and maintain a love relationship with their Portuguese consumers, as well as, be aware of the inherent benefits of those relationships. In this sense, the methodology starts by a qualitative research – twenty in-depth interviews- , followed by a quantitative research – which gathered three hundred and eighty-seven valid responses to the online survey. Since a gap was found in the literature regarding Brand Love in Portugal, the qualitative research has the purpose to achieve the relevant variables related to this construct, as a mean to improve the design of further quantitative instrument of research. After the analysis of the results, it was possible to conclude that self-expressiveness and trust revealed to be the attributes that lead to highest level of love felt by Portuguese consumers toward brands. Additionally, this construct it is also positively influenced by innovation, hedonic value and the identification between the consumer and the brand. Consequently, a Portuguese consumer in love with a brand, assumes higher levels of loyalty, engagement on positive word-of-mouth and willingness to pay a premium price for that brand.